2022
DOI: 10.20452/pamw.16304
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox present with genital ulcers-challenging clinical problem

Abstract: Sexually transmitted infections (STIs), due to the different reasons, have increased in frequency during the last 10 years and show to be major public health problem [1]. Not only well know pathogens such as Treponema pallidum, Neisseria gonorrhea or Chlamydia trachomatis, but also not typically transmitted by sexual route such as HAV, HCV, Shigella dysentriae must be taken into consideration during differential work-up [1]. Health-care professionals should be aware of the risk of emerging new STIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…122 And genital rashes were observed in many cases, which was also recently proven in another studies. [264][265][266][267][268][269][270] Other recent reports describe similar clinical characteristics. 180,271,272 Patel and colleagues 272 demonstrated that all 197 monkeypox infection cases developed mucocutaneous lesions, typically in the genitals (111 of 197 patients) or the perianal areas, causing rectal pain and penile edema.…”
Section: Clinical Characteristicssupporting
confidence: 61%
“…122 And genital rashes were observed in many cases, which was also recently proven in another studies. [264][265][266][267][268][269][270] Other recent reports describe similar clinical characteristics. 180,271,272 Patel and colleagues 272 demonstrated that all 197 monkeypox infection cases developed mucocutaneous lesions, typically in the genitals (111 of 197 patients) or the perianal areas, causing rectal pain and penile edema.…”
Section: Clinical Characteristicssupporting
confidence: 61%
“…Among the 46 included articles, 32–77 4 articles 32,33,38,43 reported cases with onset in late 2019 and 2021 and the rest reported cases with onset in 2022. We thought to include the cases from late 2019 and 2021 as they closely resembled the newer cases, and seem to be the predecessors of the current outbreak in terms of their time of onset, so their data would be useful for further patient identification.…”
Section: Resultsmentioning
confidence: 99%
“…The patient was reluctant to provide the details of the casual sexual contact for contact tracing even though the State Public Health Law Cap 106 laws of Rivers State 1999, require the mandatory disclosure of all necessary health information to the health care provider that would be useful for the containment of infectious diseases. However, enforcement and prosecution are quite difficult in the circumstance when patients are ill [23]; yet the right to care, confidentiality, consent and social acceptability are complex factors that influence disease patterns [24]. In the future, it beckons for other legal alternatives beyond counseling to ensure complete disclosure of information relevant to disease containment once public health safety is contextually considered supreme.…”
Section: Discussion On Mpox Case Reportmentioning
confidence: 99%